(untitled) (Global Journal of Science Frontier Research, 2020)
The paper investigated the effect of institutional factors on crop farmer’s participation in agricultural insurance scheme in South Western, Nigeria. Specifically, the study the study described the socio-economic characteristics of crop farmers in the study area, examined the level of awareness of the crop farmers, analyzed the factors influencing the participation of crop farmers and intensity of use of the agricultural insurance policy and compare the income between the participating and non-participating crop farmers in the study area. Multistage sampling techniques was used to select 240 respondents in the study area. Primary data were used for the study which were sourced from cross-sectional survey of crop farmers in the study area with the aid of well-structured questionnaire. The data were analysed using descriptive, Cragg’s (double-hurdle) model and t-test.